2017
DOI: 10.1007/s40544-017-0172-8
|View full text |Cite
|
Sign up to set email alerts
|

Friction characteristics of mechanically exfoliated and CVD-grown single-layer MoS2

Abstract: Abstract:In this work, the friction characteristics of single-layer MoS 2 prepared with chemical vapor deposition (CVD) at three different temperatures were quantitatively investigated and compared to those of single-layer MoS 2 prepared using mechanical exfoliation. The surface and crystalline qualities of the MoS 2 specimens were characterized using an optical microscope, atomic force microscope (AFM), and Raman spectroscopy. The surfaces of the MoS 2 specimens were generally flat and smooth. However, the Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 53 publications
5
42
0
Order By: Relevance
“…[ 11,12 ] Therefore, researchers in the field of tribology have conducted extensive research on the friction properties and wear resistance of nanomaterials. [ 11,13,14 ] 2D materials with layered structure include single‐layer or multi‐layer with atomic thickness and ultra‐low shear strength. They have the characteristics of large specific surface area, high in‐plane strength, weak interlayer interaction and good surface chemical stability, and thus have very low friction and wear‐resisting properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 11,12 ] Therefore, researchers in the field of tribology have conducted extensive research on the friction properties and wear resistance of nanomaterials. [ 11,13,14 ] 2D materials with layered structure include single‐layer or multi‐layer with atomic thickness and ultra‐low shear strength. They have the characteristics of large specific surface area, high in‐plane strength, weak interlayer interaction and good surface chemical stability, and thus have very low friction and wear‐resisting properties.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, when 3D graphene and 2D h‐BN are added into the base oil as lubrication additives, it is essential to ensure that the 3D graphene and the 2D h‐BN nanoparticles are uniformly dispersed in the base oil without any agglomeration. [ 13 ] At present, two methods are mainly used to solve the agglomeration problem. First, the uniform dispersibility of graphene in the base lubricating oil can be improved by the dispersant.…”
Section: Introductionmentioning
confidence: 99%
“…Although these methods have shown great potential in producing large-scale atomically-thin films, several problems including the crystalline quality and grain boundary structure still remain as compared to the pristine materials produced via mechanical exfoliation methods [29,35]. For example, CVD-growth MoS 2 was recently found to exhibit poor friction characteristics compared to that of pristine MoS 2 [36]. To improve the quality of the CVD-growth MoS 2 , efforts have been made to optimize the deposition conditions using the frictional behavior for pristine materials as the guideline [36].…”
Section: Introductionmentioning
confidence: 99%
“…Recent nanoscale experiments have revealed that layered materials, down to one atomic layer, also show outstandingly low surface friction when they slid against other counter surfaces [22,28]. Asides weak interlayer interaction, regular atomic arrangements are also known to impact these materials with the potential to achieve super-low friction, otherwise known as superlubricity [29,30]. Also, regarding few-layered 2D materials, it has been shown that the static frictional force gradually increases for a few initial atomic periods before reaching a steady value.…”
Section: Characteristics Of 2d Materialsmentioning
confidence: 99%